2022
DOI: 10.3389/fimmu.2022.891424
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Functional Molecule on Plasmacytoid Dendritic Cells Is Associated With HBsAg Loss in HBeAg-Positive Patients During PEG-IFN α-2a Treatment

Abstract: ObjectiveThe ideal endpoint of antiviral therapy in chronic hepatitis B (CHB) patients is to clear hepatitis B surface antigen (HBsAg). This study aimed to evaluate whether the expression of functional molecules on plasmacytoid dendritic cells (pDCs) is associated with HBsAg loss in HBeAg-positive patients during peginterferon alpha-2a (PEG IFN α-2a) therapy.MethodsA single-center prospective cohort study was performed in HBeAg-positive CHB patients who were treated with PEG-IFN α-2a and followed up for 4 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our previous study on the immune function of HBeAg positive chronic hepatitis B patients found that the frequency of pDCs was related to the incidence of CHB, the lower the frequency of pDCs in CHB patients, the more likely they were to develop hepatitis. However, we did not distinguish immature pDCs and mature pDCs frequency changes on the impact of hepatitis in this study ( 7 , 22 ). Our previous retrospective study and this prospective study both suggest that postpartum liver dysfunction is common in women with chronic HBV infection, we also found that the abnormal liver function of HBV infected women mainly occurred in 6-12 weeks postpartum ( 23 , 24 ), which indicated the importance of preventing postpartum hepatitis.…”
Section: Discussionmentioning
confidence: 60%
“…Our previous study on the immune function of HBeAg positive chronic hepatitis B patients found that the frequency of pDCs was related to the incidence of CHB, the lower the frequency of pDCs in CHB patients, the more likely they were to develop hepatitis. However, we did not distinguish immature pDCs and mature pDCs frequency changes on the impact of hepatitis in this study ( 7 , 22 ). Our previous retrospective study and this prospective study both suggest that postpartum liver dysfunction is common in women with chronic HBV infection, we also found that the abnormal liver function of HBV infected women mainly occurred in 6-12 weeks postpartum ( 23 , 24 ), which indicated the importance of preventing postpartum hepatitis.…”
Section: Discussionmentioning
confidence: 60%
“…The TLR9, MyD88, and NF-κB in PDCs are significantly downregulated, type I IFN level is decreased, and immune function is defective ( Zhu et al., 2021 ). The increased frequency of PDCs and high expression of CD86 after treatment help achieve a functional cure ( Cao et al., 2022 ). HBV also induces DCs to produce IL-10, which in turn mediates immune tolerance.…”
Section: Innate Immunity Cells In Patients With Chronic Hepatitis Bmentioning
confidence: 99%
“…The IFN therapy has been established as a useful treatment for many diseases such as hepatitis C, hepatitis B, and multiple myeloma (Ettari et al, 2016;Ye and Chen, 2021;Cao et al, 2022;Liu, H. et al, 2022). However, IFN-I treatment is known to induce various neuropsychiatric symptoms, and depression is known to occur at a high frequency of 30% or more (Tovey and Lallemand, 2010;Pinto and Andrade, 2016;Liu et al, 2020).…”
Section: Type I Interferonmentioning
confidence: 99%